2021
DOI: 10.2217/pgs-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Multi-Gene Pharmacogenetic Testing for Pain Management in Oncology Palliative Medicine

Abstract: Aim: We evaluated the application and clinical impact of multi-gene pharmacogenetic testing in oncology palliative medicine. Patients & Methods: In a single-arm pilot trial, cancer patients with uncontrolled pain were assessed in a palliative medicine clinic at baseline and received pharmacogenetic testing. Results were used as applicable up to the final visit (day 30). Pain scores, opioid prescribing, and use of pharmacogenetic test results were collected. Results: In 75 patients, the median baseline pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…36,37 While our study used a reactive approach to genotyping, some institutions are genotyping prospectively for CYP2D6 and other pharmacogenes to inform future therapies. 38,39 Indeed, our…”
Section: Lessons Learned: Clinical Implementationmentioning
confidence: 90%
See 1 more Smart Citation
“…36,37 While our study used a reactive approach to genotyping, some institutions are genotyping prospectively for CYP2D6 and other pharmacogenes to inform future therapies. 38,39 Indeed, our…”
Section: Lessons Learned: Clinical Implementationmentioning
confidence: 90%
“…While our study used a reactive approach to genotyping, some institutions are genotyping prospectively for CYP2D6 and other pharmacogenes to inform future therapies 38,39 . Indeed, our physician authors reported that not having results and accompanying recommendations at the time of enrollment was a major barrier to implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PGx‐guided supportive care has been reported with opioids to help mitigate cancer‐related pain, prophylactic use of voriconazole in intermediate to high infection risk hematological malignancies, and ondansetron for chemotherapy‐induced nausea and vomiting (CINV). 19 , 20 , 21 , 22 , 23 , 24 , 25 Institutions are increasingly implementing panel‐based PGx tests to preemptively guide medications with CPIC guidelines. 26 , 27 , 28 However, utilization of a panel‐based PGx approach to specifically guide supportive care medications in patients with cancer has not been widely described.…”
Section: Introductionmentioning
confidence: 99%
“…PGx‐guided therapy could guide the use of medications most likely to be effective, thereby reducing unnecessary medical complications and financial strain, as well as improve QoL. The use of PGx‐guided supportive care has been reported with opioids to help mitigate cancer‐related pain, prophylactic use of voriconazole in intermediate to high infection risk hematological malignancies, and ondansetron for chemotherapy‐induced nausea and vomiting (CINV) 19–25 . Institutions are increasingly implementing panel‐based PGx tests to preemptively guide medications with CPIC guidelines 26–28 .…”
Section: Introductionmentioning
confidence: 99%